(untitled) (Western Journal of Medical and Biomedical Sciences, 2025)
Geriatric populations in rural Nigeria face disproportionately high risks from blunt abdominal trauma (BAT) due to physiological fragility, limited healthcare access, and socioeconomic marginalization. This retrospective cohort study analyzed 32 patients aged >65 years admitted with BAT at Alex Ekwueme Federal University Teaching Hospital (AEFUTHA), Abakaliki, a referral center for southeastern Nigeria’s agrarian communities, where geriatric patients accounted for 32.1% of all BAT cases over a two-year period (2022–2023). Data on demographics, injury mechanisms, clinical management, and outcomes were extracted from hospital records and analyzed using SPSS v28. The cohort (median age: 73 years, IQR: 68–79) was predominantly male (65.6%, n=21) and engaged in subsistence farming (81.3%, n=26). Falls (40.6%, n=13), assaults (25.0%, n=8), and road crashes (18.8%, n=6) were the primary injury mechanisms. Delayed hospital presentation (>24 hours) occurred in 84.4% (n=27) of cases, with 53.1% (n=17) initially seeking traditional healers. Clinically, 68.8% (n=22) presented with baseline anemia (Hb <8 g/dL), and 43.8% (n=14) exhibited hemodynamic instability (SBP <90 mmHg). Hollow viscus perforations (34.4%, n=11) and hepatic/splenic injuries (28.1%, n=9) predominated. All patients required laparotomy, but 87.5% (n=28) experienced surgical delays (>24 hours post-admission) due to financial constraints. Mortality reached 37.5% (n=12), primarily from sepsis (75.0%, n=9). Catastrophic health expenditure (CHE) affected 96.9% (n=31) of families, with 59.4% (n=19) selling livestock to fund care. Geriatric mortality quadrupled adult rates (37.5% vs. 9.4%), with multivariate logistic regression identifying baseline anemia (OR: 3.8), surgical delays (OR: 4.1), and CHE (OR: 2.7) as independent predictors. These findings underscore systemic failures in prehospital care, diagnostic delays, and financial toxicity as key drivers of preventable geriatric trauma deaths in rural Nigeria. Urgent interventions—including subsidized trauma insurance, community-based fall prevention programs, and task-shifting ultrasound training for rural clinicians—are needed to mitigate disparities and align with global health equity goals.